2004
DOI: 10.1007/s10350-004-0654-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Functional Results of Colonic J-Pouch and Straight Anastomosis After Low Anterior Resection for Rectal Cancer: A Five-Year Follow-Up

Abstract: J-pouch reconstruction increased reservoir function and provided better functional outcome than straight anastomosis, even five years after surgery, especially in patients whose anastomosis is less than 4 cm from the anal verge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…Hida et al [30] reported the long-term benefits of colonic J-pouch reconstruction suggesting that it improves reservoir function to a greater extent than straight anastomosis does, especially in patients in whom the anastomosis is less than 4 cm from the anal verge. In addition, Dennett et al [31] reported that colonic J-pouch is effective in very low rectal cancer surgery, causing apparent reduction in the incidence of anastomotic leaks and in bowel frequency.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Hida et al [30] reported the long-term benefits of colonic J-pouch reconstruction suggesting that it improves reservoir function to a greater extent than straight anastomosis does, especially in patients in whom the anastomosis is less than 4 cm from the anal verge. In addition, Dennett et al [31] reported that colonic J-pouch is effective in very low rectal cancer surgery, causing apparent reduction in the incidence of anastomotic leaks and in bowel frequency.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Some studies [12,13] have reported that pouch reconstruction has an influence on the reduction of fragmentation in the shorter term but does not have effects on it in the longer term. However, since other studies [14,15] have reported that pouch reconstruction has a long-term effect on the reduction of fragmentation, it is speculated that this difference may be due to the difference in patients studied. Since it has been reported that a larger pouch may cause a sense of residual stool and defecation disorders, Hida et al [16] concluded that a pouch length of 5 cm was appropriate after comparing it with a pouch length of 10 cm.…”
Section: Discussionmentioning
confidence: 79%
“…One study with a follow up period of 5 years showed a significantly less SF and imperative urge to defecate in the pouch group compared with straight colorectal anastomosis (52). In a retrospective study (45) with a follow-up of 5 years, imperative urge to defecate was less frequent in the pouch group compared with patients without a pouch.…”
Section: Clinical Long-term Resultsmentioning
confidence: 97%
“…In numerous controlled studies volumetric parameters of reservoir function, such as MTV, SV and compliance, were examined. In 13 out of 16 studies a significantly higher MTV was measured in the pouch group compared with the group without a pouch ( 5,32, 43,52,54,64,69,82,86,102,118,122,123,160,162). In most studies the patients were examined one year post-operatively.…”
Section: Colon J Pouch (Cjp)mentioning
confidence: 99%